DFT-Based Quantum Chemical Analysis of Coumarin Derivatives - More, S.; Patil, O.; Chillargikar, S.; Lalasangi, D.; Hanagodimath, S. M. (The Nucleus, 2025)
The goal of the current work is to use density functional theory (DFT) at the B3LYP level of theory, using a basis set of 6-311++G (d, p), to comprehend the physical and chemical characteristics of 6-Methoxy-4-(4-nitro-phenoxy methyl)-chromen-2-one (6MNPM) and 1-(4-nitro-phenoxy methyl)-benzo[f]-chromen-3-one (4NPMB) of coumarin derivatives. Bond lengths and bond angles, two geometrical parameters, are calculated for coumarin derivatives. We have estimated the frontier molecular orbitals (FMO). Furthermore, to shed light on the stability and chemical reactivity of coumarin derivatives, the global reactivity descriptors were computed using FMO. The molecular electrostatic potential (MEP) investigation aims to identify the coumarin molecules' preferred locations for electrophilic and nucleophilic attacks. The distribution of atomic charge in Mulliken has been performed. The nonlinear optical properties (NLO) of coumarin molecules have been calculated to assess their suitability for NLO applications. The computation of natural bonding orbital (NBO) allows the identification of the most likely intense intermolecular interactions. The analysis focused on the temperature dependency of the thermodynamic characteristics of coumarin derivatives.